PERAN PENDIDIKAN AGAMA ISLAM DALAM MENANGKAL HOAKS DAN RADIKALISME DI KALANGAN REMAJA - Dwi Rizki Rahmadani; Intan Najma Pratiwi; Yolanda Mardianti; Bambang Irawan; Asmara Yumarni (STKIP Subang, 2025)
This study discusses the increasing vulnerability of adolescents to hoaxes and radical ideologies along with the rapid development of digital media. The study aims to analyze the role of Islamic Religious Education (Pendidikan Agama Islam/PAI) in countering hoaxes and radicalism among adolescents. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with Islamic Religious Education teachers and secondary school students, classroom observations, and documentation studies including syllabi and lesson plans. The findings indicate that Islamic Religious Education plays an important role in shaping moderate religious attitudes, fostering critical thinking skills, and increasing students’ awareness in responding to religious information. Through the internalization of religious moderation values, the principle of tabayyun, and contextual learning approaches, students become more selective and responsible in receiving and disseminating information. Therefore, Islamic Religious Education has strategic potential as a means of preventing hoaxes and radicalism in the digital era.